A REVIEW ON COMPUTATIONAL FLUID DYNAMICS SIMULATION METHODS FOR DIFFERENT CONVECTIVE DRYING APPLICATIONS - Coban, Seda Ozcan; Selimefendigil, Fatih; Öztop, Hakan Fehmi Fehmi; Hepbasli, Arif (Vinca Inst Nuclear Sci, 2023)
This paper focuses on the CFD studies on one of the commonly used drying pro-cesses for different applications. First, a brief information about drying is given with determining important properties that effect drying characteristics. Next, ba-sic principles of CFD modelling are explained while capabilities of computational processing are presented. A detailed literature survey about CFD studies in con-vective drying process is then conducted. Finally, some sound concluding remarks are listed. It may be concluded that the CFD is a powerful and flexible tool that can be adopted to many different physical situations including complex scenarios, results of CFD simulations represent good predictions for fluid-flow, heat and mass transfer of various drying methods and those numerical studies can be used for validation and controlling of applicability of new drying systems.
Keywords: Moving Boundary Model; Mass-Transfer; Moisture Transfer; Macroporous Material; 2-Dimensional Heat; Numerical-Analysis; Transport Model; Hot Air; Shrinkage; Food